Application of ex-vivo expanded autologous bone marrow derived mesenchymal stem cells for repair of transected tendon in caprine - ADHIKARI, YOGITA; JADON, N S; SHUKLA, PRIYANKA; SINGH, PARUL; VERMA, A K (The Indian Journal of Animal Sciences, 2014)
Clinically healthy non-descript adult goats (18) of either sex, were divided equally in 2 groups (group A and B) to study the application of ex-vivo expanded autologous bone marrow derived mesenchymal stem cells for repair of transected tendon in caprine. The bone marrow aspirate was collected from iliac crest and mesenchymal stem cells were cultured. When the cells reached 70–80% confluency, they were harvested using 0.25% trypsin-EDTA. In both the groups, the superficial digital flexor tendon (SDFT) was transected. In group B (test group), bone marrow derived mesenchymal stem cells (BM-MSCs) were implanted at the site of injury while in control group (group A), the operated limb was allowed to heal without BM-MSCs treatment. Post-operative care was similar in both the groups. The efficiency of treatment was evaluated by observing various clinical parameters on day 3, 7, 10, 15, 30, 45 and 60 postoperatively. The air-tendograms were performed on day 15, 45 and 60. There was early reduction in swelling, exudation, warmth and pain at the repaired site in group B. The early restoration of tendon gliding movement and weight bearing capacity were also observed in the test group as compared to the control groups. Air- tendograms revealed comparatively more adhesions in control group than in test group. Result concluded that autologous BM-MSCs enhance the tendon healing and thus can be used for early and better healing in cases of tendon injuries.